Job Satisfaction Survey: A Confirmatory Factorial Analysis Based on Vocational Colleges Teachers Sample - Mustafa, Mohamad Zaid; Buntat, Yahya; Ahad, Rosnee; Abdul Razzaq, Abdul Rasid; Bokhari, Norzella (Journal of Technical Education and Training, 2019)
This study was carried out to verify the measurement model of the construct of job satisfaction among technical teachers in Technical Vocational College Ministry of Education. A study involving 493 samples from 25 vocational colleges and comprising technical teachers in electrical and electronics engineering, civil engineering and mechanical engineering. The Structural Equation Modelling (SEM) approach with AMOS 20 software has been applied in this study. The original item was the adaptation of the Job Satisfaction Survey (JSS) questionnaire developed by Spector (1997), there were 32 items, after exploratory factor analysis was carried out 32 original items had decreased to 22 items, sub construct was also changed from 8 sub constructs to 4 sub construct only. To ensure that the job satisfaction measurement model can be verified, three factors have been evaluated, unidimensional, validity and reliability. After 10 items were dropped out, the data were re-analysed and the findings showed that all 22 items in the measurement model had factor loading meet the required level, all AVE values also meet the required level. While fitness indexes for Absolute Fit, Incremental Fit and Parsimonious Fit all meet the requirements set for all CR values â‰¥ 0.6. Overall, it can be concluded that after the measurement model was modified by dropping 3 items with factor loading <0.6 then the model was fit to be used for structural model analysis process.